Simplificação no tratamento da fratura de ângulo mandibular por meio do acesso intrabucal - Faverani, Leonardo Perez [UNESP]; Ferreira, Gabriel Ramalho [UNESP]; Polo, Tárik Ocon Braga [UNESP]; Gaetti-Jardim, Ellen Cristina [UNESP]; Okamoto, Roberta [UNESP]; Aranega, Alessandra Marcondes [UNESP]; Assunção, Wirley Gonçalves [UNESP]; Garcia Júnior, Idelmo Rangel [UNESP] (My University, 2012)
Mandibular fractures are the injury most commonly found in the facial bones. They have varied etiology, such as automobile, motorcycle and cycling accidents, physical abuse and falls. The choice of treatment of mandibular fractures most often employed is the reduction and fixation of bone fragments. Regarding fractures involving the mandibular angle, access headgear is the most widely used, in view of the action of masticatory muscles causing greater displacement of fractured stumps. Therefore, the proposal to introduce a conservative approach and facilitated for the treatment of fractures of the mandibular angle, as well as to demystify the contraindication to intraoral approach cases unfavorable fracture displacement, this work is to report a clinical casesurgical mandibular angle fracture, treated by intraoral approach. The fracture was fixed with two plates, one following the external oblique line system (1.5 mm) and a lower system (2.0 mm), with the help of percutaneous trocar. This approach is very promising for these cases, in order to ease the technical as well as by reducing the technical complications of extraoral approach.

As fraturas mandibulares são as injúrias mais comumente encontradas nos ossos da face. Possui etiologia variada, destacando-se os acidentes automobilísticos, ciclísticos, motociclísticos, as agressões físicas, quedas, dentre outras. A opção de tratamento mais empregada das fraturas mandibulares consiste na redução e fixação dos fragmentos ósseos. No tocante as fraturas envolvendo o ângulo mandibular, o acesso extrabucal é o mais empregado, tendo em vista a ação da musculatura mastigatória que provoca maior deslocamento dos cotos fraturados. A proposta de uma abordagem conservadora e facilitada para o tratamento das fraturas de ângulo mandibular é apresentada. Também, desmistificar a contra-indicação do acesso intrabucal para os casos de fraturas desfavoráveis ao deslocamento. Este trabalho, além disso, vem relatar um caso clínico-cirúrgico de fratura do ângulo mandibular, tratado por meio do acesso intrabucal. Fixou-se a fratura com duas placas, sendo uma acompanhando a linha oblíqua externa (sistema 1,5 mm) e, outra mais inferior (sistema 2,0 mm), com o auxílio do trocater percutâneo. Esta abordagem é bastante promissora para estes casos, tendo em vista a maior facilidade da técnica, bem como pela redução das complicações inerentes à técnica pelo acesso extrabucal.
Simplification in the treatment of mandibular angle fracture trhough intraoral approach
Keywords: Mandibular fracture; Epidemiology; Treatment; Fratura mandibular; Epidemiologia; Tratamento